2023
DOI: 10.3390/su15065179
|View full text |Cite
|
Sign up to set email alerts
|

Which Assessment of Coach-Created Motivational Climate Better Predicts Young Athletes’ Engagement over a Season? Athletes’ Perceptions and Match Observations Do

Abstract: This work examines athletes’ and coaches’ perceptions and observed behavior in training and matches of the motivational climate created by the coach over the course of a season and whether these sources of information can inform the engagement of young basketball and volleyball players. A longitudinal design and multilevel mixed-effects linear regression models were conducted. Adolescents (n = 517) of both genders (61.1% male, 38.9% female) aged between 12 and 20 years (M = 16.01; SD = 1.85) playing in the A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Additionally, the cross-sectional design does not allow for follow-up engagement over time. Longitudinal studies have measured engagement over a season, examining antecedents such as variables in the environment, including the athlete–coach relationship [ 19 ]. Follow-up studies of athletes’ careers could provide information about the predictive validity of the construct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the cross-sectional design does not allow for follow-up engagement over time. Longitudinal studies have measured engagement over a season, examining antecedents such as variables in the environment, including the athlete–coach relationship [ 19 ]. Follow-up studies of athletes’ careers could provide information about the predictive validity of the construct.…”
Section: Discussionmentioning
confidence: 99%
“…This study also provides coaches, parents, and sports leaders with valuable knowledge and resources to enhance positive sporting experiences and promote health. Following several studies that have shown the significance of the creation of motivational climates by coaches and their impact on engagement, particularly in what happens during competitions and matches [ 19 ], it opens the way for intervention, providing specific strategies to develop in these contexts to support autonomy and promote task-involving climates. For instance, coaches can set challenging and intrinsically motivating goals and establish a line of learning for each athlete to evaluate their progress.…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coaches believe that they provide greater support and active management and lower negative feedback and passive management than their athletes perceive. Coaches perceive their leadership behavior more positively than their team athletes ( Gjesdal et al, 2019 ; Raimundi et al, 2023 ). It is worth noting that this pattern was verified in objective 1, where coaches were more optimistic about their tendency to explicitly the leadership philosophy than athletes’ perception.…”
Section: Discussionmentioning
confidence: 99%